Pengaruh Likuiditas, Solvabilitas, Profitabilitas dan Risiko Pasar Terhadap Return Saham Perusahaan Sektor Consumer Goods di Bursa Efek Indonesia Periode 2019/2020 - Diah Ayu Wulan Fitriana; Gendro Wiyono; Pristin Prima Sari (Universitas Batanghari Jambi, 2023)
Financial performance is an analysis used to assess how a company carries out its obligations and its financial implementation rules. The purpose of this study was to analyze the influence of liquidity, solvency, profitability and market risk on stock returns of consumer goods companies in the food and beverage subsector for the 2019-2020 period. The data analysis method used is descriptive analysis, classical assumption test, multiple linear regression, coefficient of determination, t test and F test. From the descriptive analysis, the min value is obtained; max; mean; std. deviation CR= 0.411; 13.267; 2,851; 2.822, DER= -2.127; 5.37; 0.855; 1.061, ROA = -0.154; 0.607; 0.098;0.147, Market Risk = -561; 966; 224,581; 345;766, Stock Return = -0.749; 1.321, 0.026; 0.381. In the classical assumption test, the result was that this study occurred normally, there was no multicollinearity, no autocorrelation and no heteroscedasticity. From multiple linear regression, we get the regression equation Y = -0.202 + 0.007CR + 0.045DER + 1.630ROA + 4.982 Market Risk + 0.120 std, error. The coefficient of determination produces an adjusted R of 0.271, which means that the contribution of the CR, DER, ROA and Market Risk variables has an effect on the dependent variable stock return of 27.1%. CR, DER and Market Risk t tests have no significant effect on stock returns, while ROA has a significant effect on stock returns. Simultaneously CR, DER, ROA and Market Risk affect stock returns.